Exhaustivity, Focus and Incorporation in Hungarian - Gáspár, Edgar Onea (Proceedings of the Amsterdam Colloquium, 2007)
There are two influential assumptions about Hungarian focus interpretation: i) in Hun garian two types of focus (information and identificational focus) are distinguished and ii) the pre-verbal focus in Hungarian has a strictly exhaustive reading encoded in a cov ert operator. In this paper I will sketch an alternative analysis of the Hungarian data showing that neither of the two assumptions needs to be maintained. I will argue that the particularities of “Hungarian focus” can be best accounted for by assuming presup positional effects related to word order at the level of the verbal predicate.